Effect of Centrifugation on the Stability of Nanoemulsion Base Containing Tween 80, PEG 400, Poloxamer 188, and DMSO - Karmila Lihawa; Mohamad Adam Mustapa; Mohamad Aprianto Paneo; Widy Susanti Abdulkadir; Muhammad Taupik (Jurnal Literasi Mandiri, 2026)
Nanoemulsions are biphasic dispersion systems (oil and water) with nanometer-scale droplet sizes that exhibit better physical stability than conventional emulsions and are widely utilized in pharmaceutical and cosmetic applications. The kinetic stability of nanoemulsions is strongly influenced by the composition of surfactants, co-surfactants, and other supporting components. This study aimed to evaluate the effect of centrifugation on the physical stability of an olive oil–based nanoemulsion with varying concentrations of Tween 80 and PEG 400, supported by Poloxamer 188 and DMSO. This laboratory-based experimental study employed the aqueous titration method for nanoemulsion preparation, followed by ultrasonication for 60 minutes. Accelerated stability testing was conducted through centrifugation at speeds of 2,000, 4,000, 6,000, and 8,000 rpm for 30 minutes. Physical evaluations included organoleptic testing, pH measurement, viscosity determination, and emulsion type identification using the methylene blue dye method. The results showed that all formulations remained stable at 2,000–4,000 rpm. At 6,000 rpm, formulations F1 and F2 began to exhibit partial creaming, and at 8,000 rpm significant phase separation was observed in F1 and F2, whereas F3 and F4 remained clear and homogeneous. The pH values of all formulations ranged from 6.8 to 7.3 (7.03 ± 0.22), indicating good chemical stability. Viscosity values ranged from 103 to 132 cPs (111.5 ± 13.77), which fall within the acceptable range for nanoemulsion systems. The emulsion type test showed a homogeneous blue color distribution, confirming that all formulations were oil-in-water (O/W) systems. In conclusion, the ratio of Tween 80 to PEG 400 plays a crucial role in enhancing the kinetic stability of olive oil–based nanoemulsions. Formulations F3 and F4 demonstrated the most optimal physical stability and have strong potential for further development in pharmaceutical and cosmetic applications.